MAINSET REVOLUTION: RELATIONSHIPS AND PARTICIPATION FOR THE KINGDOM OF GOD - Arip Supri Sitompul; Sarjani Jojor Martua Sianturi; Jon Roi Tua Purba; Kepler Sianturi; Novalina S Silaban (RADJA PUBLIKA, 2025)
Awareness of the Kingdom of God demands a holistic transformation within the lives of believers. This transformation encompasses not only the spiritual dimension but also the renewal of mindset and practical actions that align with Gospel values. This study, entitled